Evaluating the Success of Project Management Information Systems’ Comprehensive Planning in Industrialized Building Systems - Taherkhani, Roohollah (Salehan Institute of Higher Education, 2018)
The main reason for the failure of most of management information systems is referred to the problems that arise from management factors and strategic components, expectations, complexity, and risks. Finally, the main applicable proposal is giving importance by managers and analysts to the fit between organization and its information system as well as giving attention to training categories in implementation of information system, preparing financial supports and human resource in design, implementation, and development of information system, strengthening progressive factors, and weakening restrictive factors in organization by management to design or develop the system and finally, preparing organizational infrastructures to implement information system. Introduction of an information system has a strong managerial, organizational, and technological impact on industrial building methods. One of the objectives of this study was to identify and introduce key success factors of Project Management Information Systems (PMIS) in Industrialized Building Systems (IBS). The results of hypotheses showed that all dimensions of PMIS influence the performance of projects. But in the second phase of the study, sub-factors were classified using hierarchical analysis approach. This classification helps managers to identify the most important factors and obtain better results concentrating on the main factors compared with using PMIS.